Polymerization of ethylene to branched poly(ethylene)s using ansa-eta(5)-monofluorenyl cyclohexanolato zirconium(IV) complex/methylaluminoxane - Rajesh, A.; Sivaram, S. (Polymer Bulletin, 2011)
ansa-eta(5)-Monofluorenyl cyclohexanolato zirconium complex 3 was shown to be active for the polymerization of ethylene when activated with methylaluminoxane (MAO) at 5 bar. Up to a polymerization temperature of 40 A degrees C, 3/MAO resulted in linear poly(ethylene)s with saturated chain ends. However, at polymerization temperatures of 60, 80, and 100 A degrees C, a mixture of branched poly(ethylene)s, linear alpha-olefins and long chain alkanes was obtained. The poly(ethylene)s produced at 80 and 100 A degrees C exhibited a bimodal molecular weight distribution indicative of multiple active species. Very high molecular weight (M (v) > 5 x 10(5)) linear poly(ethylene)s were obtained using 3/MAO at 25 A degrees C.
Keywords: ansa-Monofluorenyl complex; Bimodal MWD; Branched poly(ethylene)s; Ethylene polymerization; Methyl aluminoxane

Polymerization of ethylene using amido functional half-sandwich complexes of group 4 metals - Rajesh, A.; Sivaram, S. (Polymer Engineering and Science, 2011)
Ligands (C(13)H(9))(2,6-R(2)C(6)H(3)NH)SiPh(2) [R = (i)Pr (2a), Me (2b)] were synthesized by single deprotonation of the amino group in 2,6-dialkylanilines with n-BuLi at -78 degrees C followed by reaction with fluorenyl diphenyl silyl chloride [FluSi(Ph(2))Cl]. Single crystal X-ray diffraction studies revealed different geometries around the nitrogen atom for the two compounds. Titanium and zirconium complexes (3a-3d) were prepared by double deprotonation of the ligands with n-butyl lithium (n-BuLi) followed by reaction with the respective metal chlorides, MCl(4) (THF)(2). Polymerization of ethylene was performed using these complexes as catalyst precursors along with methylaluminoxane (MAO) as an activator at 5 bar pressure. Complexes 3a-3d/MAO exhibited moderate catalyst activities for polymerization of ethylene and resulted in high molecular weight linear poly(ethylene)s (M(v) > 4 3 10(5) g/mol). Catalyst activities were much lower when compared to similar N-alkyl substituted complexes presumably due to the resonance effect of the aromatic group on the amido nitrogen. POLYM. ENG. SCI., 51:2103-2108, 2011. (C) 2011 Society of Plastics Engineers